Growth and yield of curly red chili (Capsicum annum L.) in response to mulching and chicken manure application in the erosion-prone area of Loto, Ternate island - Hartati, Tri Mulya; Ishak, Lily; Aji, Krishna; Roini, Chumidach (Universitas Padjadjaran, 2025)
Information on soil resources in volcanic landscapes presents a high potential for agricultural land development, but its development is always faced with the potential for continuous land degradation. This study aims to reduce the rate of land degradation through the application of vegetative conservation in erosion-prone Loto agrotourism area, Ternate Island. The research location is focused on erosion-prone areas. The research consisted of a soil resource inventory and a vegetative conservation application. The vegetative conservation application method used a Randomized Block Design (RBD) pattern, composed of 2 factors. The first factor is mulching, namely: no mulching (M0) and mulching (M1), while the second factor is chicken manure-based organic fertilizer, specifically at 10 tons ha-1(P1), and 20 tons ha-1(P2). Observation parameters include soil parameters as well as plant growth and yield parameters. The results showed that the combination of mulching and chicken manure had an insignificant effect on plant height, number of flowers, number of fruits, or number of branches. However, the application of mulching was found to increase the fruit weight of curly chili plants. This finding implied that erosion-prone areas require improved land management, such as mulching, to optimize soil resources and reduce erosion risk.